1979
DOI: 10.1071/pp9790459
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Uptake by Barley Seedlings

Abstract: Arsenate uptake consists of a rapid, apparently irreversible, initial phase followed by a less rapid 'steady state' phase, both of which are temperature sensitive and strongly inhibited by phosphate. By comparison, 'steady state' uptake of phosphate was only weakly inhibited by arsenate. The initial and 'steady state' phases of arsenate uptake were highly correlated (R = 0.958, P < 0.001). Arsenite also appeared to exhibit initial and 'steady state' uptake phases but uptake was slower by a factor of 3-4 tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
121
0
6

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(136 citation statements)
references
References 0 publications
9
121
0
6
Order By: Relevance
“…It can be inferred that the AM fungus can enhance host plant P nutrition while suppressing plant As uptake, and this agrees with a recent study by Chen et al (2007). Plants take up arsenate via the phosphate uptake system (Asher and Reay, 1979;Meharg andMacnair, 1990, 1992) and the suppression of high affinity P uptake therefore assists plants to enhance arsenate tolerance (Meharg and Macnair, 1992). Interestingly, AMF can Table 2 P and As contents and molar P/As content ratios of non-mycorrhizal and mycorrhizal M. truncatula colonized by G. mosseae Added As (mg kg À1 ) P content (mg pot À1 ) As content (mg pot À1 ) P/As content ratio (mol P/mmol As) 0.09 AE 0.02b 0.37 AE 0.11c Inoculation P < 0.001 P < 0.01 P < 0.001 As level P < 0.001 P < 0.001 P < 0.001 Interaction P < 0.001 P < 0.001…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It can be inferred that the AM fungus can enhance host plant P nutrition while suppressing plant As uptake, and this agrees with a recent study by Chen et al (2007). Plants take up arsenate via the phosphate uptake system (Asher and Reay, 1979;Meharg andMacnair, 1990, 1992) and the suppression of high affinity P uptake therefore assists plants to enhance arsenate tolerance (Meharg and Macnair, 1992). Interestingly, AMF can Table 2 P and As contents and molar P/As content ratios of non-mycorrhizal and mycorrhizal M. truncatula colonized by G. mosseae Added As (mg kg À1 ) P content (mg pot À1 ) As content (mg pot À1 ) P/As content ratio (mol P/mmol As) 0.09 AE 0.02b 0.37 AE 0.11c Inoculation P < 0.001 P < 0.01 P < 0.001 As level P < 0.001 P < 0.001 P < 0.001 Interaction P < 0.001 P < 0.001…”
Section: Resultssupporting
confidence: 91%
“…both compete for the same sorption sites on soil particles (Adriano, 2001). Uptake of As and P by plants and microorganisms is shown to be mediated by the same transporters (Asher and Reay, 1979;Willsky and Malamy, 1980a,b;Meharg andMacnair, 1990,1992;Bun-ya et al, 1996;Rosen, 2002), and thus enhanced plant acquisition of P may also lead to enhanced acquisition of As. Gonzalez-Chavez et al (2002) reported enhanced arsenate resistance of both tolerant and nontolerant plants colonized by AMF associated with suppression of high-affinity arsenate/phosphate transporters and decreasing arsenate uptake.…”
Section: Introductionmentioning
confidence: 97%
“…The addition of 1 mM Si to the uptake solution did not change the K m value as compared to the treatment with no Si, but the V max was decreased by nearly 50% (Table 3), indicating that the effect of Si on As uptake was not mediated by a direct competitive effect of Si on active sites of As (P) transporter on root cell membranes. Since in many plant species As is taken up via the Pi transport systems (Asher and Reay, 1979;Meharg and Macnair, 1992), the alternative reason for Si-mediated reduction in As uptake could be through its inhibitory effect on P uptake. Thus, factors affecting P uptake might also affect As uptake.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that effects of Si on P uptake are somehow dependent on the external P concentrations in the nutrient solution, and are also influenced by the Si already present in the plants Takahashi, 1989, 1990). Arsenic and phosphorus are both Group V A elements, and have similar electron configurations and chemical properties (Asher and Reay, 1979;Meharg and Macnair, 1992), but it is not clear if changes in internal Si and P concentrations in uptake solution can also affect arsenate uptake by rice.…”
Section: Introductionmentioning
confidence: 99%
“…The speciation of As impacts on its bioavailability and so on its uptake and accumulation in plants. AsV is a phosphate analogue and competes for uptake through phosphate transporters (such as PHT1;1 and PHT1;4 in Arabidopsis) [4,5], whereas AsIII is taken up through aquaglyceroporins [6].…”
Section: Highlightsmentioning
confidence: 99%